The Victory of Partai Amanat Nasional (PAN) in Ngada as the Form of Public Distrust against the Party - Bertolomeus Loji Sua (Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
A political party is a political organization represented by individuals who work for the people with the ideology embraced by the party itself. The task of a political party is to provide political education and lead according to the people’s desires. But what if today’s political party has unconsciously formed the public distrust? The phenomenon of the PAN victory in Ngada district-Nusa Tenggara Timur (NTT) was a symbol of Ngada’s public distrust toward the party itself, as well as the previous political parties that had won in Ngada. This study aimed to assess the public distrust toward political parties, by looking at the phenomenon of the PAN victory in Ngada. The method used in this research was qualitative research, with in-depth interviews with sources in the field. In this study, the author found some interesting things related to the society and politics in Ngada. One of those things was that the people neither trust nor put hope in the political parties in the matter of responding to their wishes and communities’ development in Ngada. The PAN victory in Ngada was an interesting phenomenon in the political sphere that showed the public’s distrust of the parties today.